Predatory efficacy of culex (Lutzia) fuscanus on mosquito vectors of human diseases in Sri Lanka - Surendran, S.N.; Jude, P.J.; Thavaranjit, A.C.; Eswaramohan, T.; Vinobaba, M.; Ramasamy, R. (The American Mosquito Control Association, Inc., 2013)
Larvae of Culex (Lutzia) fuscanus were collected from ovitraps in a natural breeding site. Collected larvae were used to establish a self-mating colony, and larval progeny were then used to determine their predatory efficacy on larvae of 3 vector mosquito species, Aedes aegypti, Anopheles subpictus, and Cx. tritaeniorhynchus. Statistical analysis revealed that Cx. fuscanus showed greater feeding efficacy for Ae. aegypti than for Cx. tritaeniorhynchus and An. subpictus. The natural predatory role of this species can potentially be exploited for biological control of mosquito vectors in Sri Lanka.
Keywords: Culex (Lutzia) fuscanus; larvae; predatory efficacy; prey; Sri Lanka